Prolactin enhances the in vitro production of IgG in peripheral blood mononuclear cells from patients with systemic lupus erythematosus but not from healthy controls. Issue 3 (1st March 2001) - Jacobi, A M; Rohde, W; Volk, H-D; Dörner, T; Burmester, G-R; Hiepe, F
Abstract : OBJECTIVES: Recent evidence suggests that prolactin (PRL) plays a part in the pathogenesis of systemic lupus erythematosus (SLE). Because B cell hyperreactivity and autoantibodies are characteristic hallmarks of SLE, this study aimed at assessing the impact of this pituitary hormone on IgG production by stimulating peripheral blood mononuclear cells (PBMC) with PRL. METHODS: PBMC from 11 patients with SLE assessed by the ECLAM score and eight healthy controls were incubated with PRL and cultured for seven days. IgG production was measured by enzyme linked immunosorbent assay (ELISA). RESULTS: Spontaneous IgG production of SLE PBMC was significantly enhanced compared with that found in healthy controls. After PRL stimulation, the IgG concentrations of supernatants from SLE PBMC were significantly higher than those of unstimulated PBMC (median 394 ng/ml). Of note, the physiological concentration of PRL (20 ng/ml) induced IgG production more effectively (median 1139 ng/ml) than PRL at 100 ng/ml (median 1029 ng/ml). In contrast, preincubation with PRL did not stimulate IgG production in normal PBMC. A significant correlation between PRL induced IgG production and the disease activity (ECLAM) of the patients with SLE was seen. Moreover, the maximum amount of PRL induced IgG depended on the serum PRL concentrations of the patients with SLE. CONCLUSIONS: The results suggest that PBMC from patients with SLE have an extraordinarily high susceptibility to PRL, showing the most striking effect at a concentration usually found in vivo. This indicates a potential role for mild hyperprolactinaemia in the pathogenesis of SLE, influencing both IgG production and disease activity.